Circulating cytokines in active polymyalgia rheumatica. Issue 01 (1st March 2009) - Alvarez-Rodríguez, L; Lopez-Hoyos, M; Mata, C; Marin, M Jose; Calvo-Alen, J; Blanco, R; Aurrecoechea, E; Ruiz-Soto, M; Martínez-Taboada, V M
Abstract : Objective: To characterise the circulating cytokine profile and the cellular source of circulating cytokines in polymyalgia rheumatica (PMR). Methods: The study included 34 patients with active untreated PMR and 17 age-matched healthy controls (HC). Circulating cytokines were measured by cytometric bead array and ELISA. Intracellular cytokines were assessed in CD3+ and CD14+ cells by flow cytometry. Cytokines in cell culture supernatants were also determined after polyclonal stimulation of patients' peripheral blood mononuclear cells. Results: Circulating levels of interleukin-6 (IL6) were significantly higher in subjects with active PMR than in HC. Corticosteroid (CS) treatment was followed by a decrease in the level of IL6. Intracellular cytokine staining showed that circulating monocytes did not produce higher amounts of proinflammatory cytokines in patients with PMR than in HC. There was a discordance between serum levels and cytokine-producing monocyte and T cells, and it was not possible to demonstrate a Th1 bias in the peripheral compartment. Conclusions: Active PMR is characterised by increased serum levels of IL6, but not of other proinflammatory cytokines, that are rapidly suppressed by CS treatment. As circulating monocytes do not show increased production of proinflammatory cytokines, IL6 may be mainly produced in the inflamed tissue. A study of the circulating cytokine profile and its cellular source may provide a clue to new therapeutic options.